2013
DOI: 10.1111/1541-4337.12006
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Essential Oils: A Review

Abstract: In recent years, consumers have developed an ever-increasing interest in natural products as alternatives for artificial additives or pharmacologically relevant agents. Among them, essential oils have gained great popularity in the food, cosmetic, as well as the pharmaceutical industries. Constituting an array of many lipophilic and highly volatile components derived from a great range of different chemical classes, essential oils are known to be susceptible to conversion and degradation reactions. Oxidative a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
565
1
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 944 publications
(650 citation statements)
references
References 151 publications
9
565
1
4
Order By: Relevance
“…Several reports suggested the use of essential oils for controlling mites [14]. On the other hand, essential oils have gained great popularity as consumers have developed a particular ever-growing awareness toward the use of natural ingredients in food products [15][16][17]. In the current research, mites infested Ras cheese were identified.…”
Section: Introductionmentioning
confidence: 89%
“…Several reports suggested the use of essential oils for controlling mites [14]. On the other hand, essential oils have gained great popularity as consumers have developed a particular ever-growing awareness toward the use of natural ingredients in food products [15][16][17]. In the current research, mites infested Ras cheese were identified.…”
Section: Introductionmentioning
confidence: 89%
“…Certain factors are crucial for maintaining the stability of essential oils, such as temperature, light, and oxygen availability. Therefore, these factors need to be carefully considered [49].…”
Section: Miscellaneous Propertiesmentioning
confidence: 99%
“…The authors verified that the oil composition was a function of temperature and that when frozen, the oil composition underwent only minor changes, and the primary quality was maintained, demonstrating the oil degradation effect under high temperature. The ambient temperature crucially influences the essential oil stability in several respects, and as a rule, chemical reactions are accelerated with increasing temperature because the reaction rates are increased by heat [49].…”
Section: Miscellaneous Propertiesmentioning
confidence: 99%
“…This could be due to the taxonomy of the cannabis samples grown in NZ or a consequence of cannabis storage. It has been shown that the composition of terpenoids in the production of essential oils not only depends on the method of production of the oil but also on growing conditions such as soil, climate, growth stage, harvest time and previous storage of the plant material [60].…”
mentioning
confidence: 99%